If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 1 + -2n + 5 Reorder the terms: 5 = 1 + 5 + -2n Combine like terms: 1 + 5 = 6 5 = 6 + -2n Solving 5 = 6 + -2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2n' to each side of the equation. 5 + 2n = 6 + -2n + 2n Combine like terms: -2n + 2n = 0 5 + 2n = 6 + 0 5 + 2n = 6 Add '-5' to each side of the equation. 5 + -5 + 2n = 6 + -5 Combine like terms: 5 + -5 = 0 0 + 2n = 6 + -5 2n = 6 + -5 Combine like terms: 6 + -5 = 1 2n = 1 Divide each side by '2'. n = 0.5 Simplifying n = 0.5
| 4(d-5)=1 | | 5m-14=8m+4 | | 2.5x-(-8.2)=26.7 | | -8n+4(1+5)=6n-14 | | -11(x+9)=99 | | 6x^4*3x^4= | | y=-0.80(55)+136 | | 4.3*p=28.81 | | 5n-9=71 | | 5(x+4)=75 | | 6y-7=10y+25 | | y=-0.80(45)+136 | | 7(1y+-2)+8=3(1y+-4)+-2 | | y=-0.80(35)+136 | | -18-6k=6(13k) | | 2x-1=-x+5 | | 15x^3-7x-2= | | x+29=83 | | 16/7=m/21 | | 3x+5=-6 | | 0.2x-1.5=0.1 | | 3a^2+4=0 | | 16-5(3t-4)=8-(-2t+11) | | -7(-5x+7)=-49 | | 4m-4=9m | | 29=17-2x | | 3y+5=y | | 6(-6x-10)=-132 | | 3(x+1)+7(x+1)-6= | | 8x=8x+6 | | 0.5(x+4)-(10x+9)=-77 | | -4(1x+10)=-32 |